Cimifugin relieves pruritus in psoriasis by inhibiting TRPV4. (July 2021) - Yan, Jinjin; Ye, Fan; Ju, Ying; Wang, Dijun; Chen, Jiao; Zhang, Xinyu; Yin, Zhi; Wang, Changming; Yang, Yan; Zhu, Chan; Zhou, Yuan; Cao, Peng; et al.
Highlights: Psoriasis induced scratching behavior is TRPV4 dependent. Psoriasis increased TRPV4 expression in epidermis and DRG. Cimifugin relieved psoriasis itching through inhibiting TRPV4 induced calcium influx in HaCaT cells and mice DRG neurons. Abstract: Psoriasis is an immune-mediated chronic inflammatory skin disease characterized by erythema, scales, and infiltration of the skin, which causes deleterious effects on patient quality of life. TRP channel played important roles in the generation and conductance of itch signal . According to our results, psoriasis induced itch was TRPV4 dependent, and TRPV4 expression in both epidermis and DRG were up-regulated in psoriasis. Thus, TRPV4 is an attractive candidate for treating psoriasis induced itch. Cimifugin is a common compound in antipruritic Chinese medicine. In our study, GSK1016790A, a TRPV4 channel specific agonist, induced acute itch was inhibited by cimifugin in a dose-dependent manner. Furthermore, cimifugin treatment reduced the scratching behavior and reversed the TRPV4 up-regulation induced by psoriasis. In particular, cimifugin decreased GSK1016790A induced calcium response both in HaCaT cells and DRG neurons. Importantly, in TRPV4 transfected HEK293 cells, GSK101 induced calcium response was also significantly inhibited by cimifugin pretreatment. Consistent with our calcium imaging result, cimifugin pretreatment also inhibited GSK101 induced inward currents. Our study delineated a new role of TRPV4 in psoriasis and emphasized the antipruritic effect of cimifugin, which opened a new avenue to itch management in psoriasis. Graphical abstract: Image, graphical abstract